Answer:
C
Step-by-step explanation:
Take a careful look at a(n) = 6(-8)^(n-1).
The first term is 6. This is the result if we let n = 1; 6(-8)^0 = 6(1) = 6. Thus, we can immediately eliminate possible answer choices A and D.
What's the next term? Knowing that the first term, a(1), is 6, the next term is found by multiplying this 6 by (-8)^1, obtaining -48.
The next (third) term is found by multiplying this -48 by (-8)^2, obtaining -48*(+64), or - 3072.
Note that the sign of (-8)^(n-1) alternates, being odd when n-1 is odd and even when n-1 is even.
Answer C is the correct one.
You need to divide 6 by 4/5.
6÷4/5
6 x 5/4
30/4
7 2/4 = 7 1/2 answer
Answer:
At her current rate it will take here 70 minutes to finish the race
Answer:
The slope is m = 7/8 or 0.975
Step-by-step explanation: